2014
DOI: 10.1017/s175173111300181x
|View full text |Cite
|
Sign up to set email alerts
|

Fat source and dietary forage-to-concentrate ratio influences milk fatty-acid composition in lactating cows

Abstract: On the basis of the potential benefits to human health there is an increased interest in producing milk containing lower-saturated fatty acid (SFA) and higher unsaturated fatty acid (FA) concentrations, including cis-9 18:1 and cis-9, trans-11-conjugated linoleic acid (CLA). Twenty-four multiparous Holstein cows were used in two experiments according to a completely randomized block design, with 21-day periods to examine the effects of incremental replacement of prilled palm fat (PALM) with sunflower oil (SFO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Enrichment of 18:3 n‐3 in milk was highest when high amounts of processed linseeds were fed to cows fed a high concentrate diet . Similarly milk 18:2 n‐6 concentrations were found to be higher (3.84 vs. 3.36 g/ 100 g total fatty acids) when sunflower oil (30 g/kg dry matter) was included in total mixed rations containing a higher proportion of concentrates (39:61 vs. 48:52; ).…”
Section: Persistency Of Milk Fatty Acid Composition Responsesmentioning
confidence: 94%
“…Enrichment of 18:3 n‐3 in milk was highest when high amounts of processed linseeds were fed to cows fed a high concentrate diet . Similarly milk 18:2 n‐6 concentrations were found to be higher (3.84 vs. 3.36 g/ 100 g total fatty acids) when sunflower oil (30 g/kg dry matter) was included in total mixed rations containing a higher proportion of concentrates (39:61 vs. 48:52; ).…”
Section: Persistency Of Milk Fatty Acid Composition Responsesmentioning
confidence: 94%
“…We examined the effects of replacement of a saturated fat-enriched 16:0 (prilled palm fat; PPF) with an unsaturated fat rich in 18:2n-6 (sunflower oil; SO) in low-forage diets (experiment 1) or increasing the forage-to-concentrate ratio (F:C) in diets containing SO (experiment 2) on ruminal fermentation characteristics and milk OBCFA composition. The dietary effects on feed intake, digestibility, milk production and composition, and milk FA composition, except OBC-FA, were reported previously (Vazirigohar et al, 2014). Moreover, data from both experiments were used to explore the associations among ruminal VFA and milk OBCFA in cows fed diets containing supplemental fats using principal component analysis (PCA).…”
Section: Short Communicationmentioning
confidence: 94%
“…A number of studies have demonstrated that n−3 PUFA content in red meat and cow milk are higher in animals fed pasture-based compared to concentrate-based diets ( Howes et al., 2015 , Jaturasitha et al., 2016 , Shingfield et al., 2013 , Vazirigohar et al., 2014 ). Eriksson and Pickova (2007) suggested that fresh grass exerts a greater protection for n-3 PUFA against rumen microorganisms than concentrates, because of the presence of other secondary metabolites that could inhibit ruminal BH ( Alves et al., 2017 , Girard et al., 2016 , Willems et al., 2014 ).…”
Section: Omega-3 Pufa Sources For Ruminantsmentioning
confidence: 99%
“…However, forage generally contains a low level of total FA, ranging about 1–3% dry matter (DM) ( Chilliard et al., 2007 , Jaturasitha et al., 2016 ). Thus, other lipid sources are commonly supplemented to increase dietary energy density to gain improved animal performance ( Parvar et al., 2017 , Vazirigohar et al., 2014 ).…”
Section: Omega-3 Pufa Sources For Ruminantsmentioning
confidence: 99%